Pengembangan Video Kosakata Dasar Bahasa Jepang Bidang Kaigo Berbasis ARCS Di LPK Saiko Singaraja - Azzahra Novelia Khairunnisa; Ni Nengah Suartini; Irvina Restu Handayani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
This study is a Research and Development (R&D) project aimed at developing instructional videos for basic Japanese vocabulary in the kaigo (caregiver) field and testing their feasibility for candidate specified skilled workers at LPK Saiko Singaraja, Bali. The developed media consist 13 learning videos, each containing vocabulary introduction, pronunciation practice, and quiz exercises. This research employs the ADDIE development model, which consist of five stages Analyze, Design, Development, Implementation, and Evaluation. The video development is based on Attention, Relevance, Confidence, Satisfaction (ARCS) motivational theory. Research data were collected through interviews, need questionnaires, and validation questioners involving material experts, media experts, instructors, and students. The validation result showed an average score of 95,83 (Highly Appropriate) from material expert, 93,75 (Highly Appropriate) from media experts, 100 (Highly Feasible) from instructor, and 100% (Highly Feasible) from students. Based on these results, it is concluded the ARCS based basic Japanese vocabulary learning videos are feasible as an alternative medium to support the learning of candidate specified skilled workers in the kaigo field at LPK Saiko Singaraja.